The Reversible Electron Transfer Within Stimuli-Responsive Hydrochromic Supramolecular Material Containing Pyridinium Oxime and Hexacyanoferrate (II) Ions - Blaženka Foretić; Teodoro Klaser; Juraj Ovčar; Ivor Lončarić; Dijana Žilić; Ana Šantić; Zoran Štefanić; Alen Bjelopetrović; Jasminka Popović; Igor Picek (Molecules)
The structural and electronic features of the stimuli-responsive supramolecular inter-ionic charge-transfer material containing electron accepting N-benzylyridinium-4-oxime cation (BPA4+) and electron donating hexacyanoferrate (II) are reported. The study of reversible stimuli-induced transformation between hydrated reddish-brown (BPA4)4[Fe(CN)6]·10H2O and anhydrous blue (BPA4)4[Fe(CN)6] revealed the origin of observed hydrochromic behavior. The comparison of the crystal structures of decahydrate and anhydrous phase showed that subsequent exclusion/inclusion of lattice water molecules induces structural relocation of one BPA4+ that alter the donor-to-acceptor charge-transfer states, resulting in chromotropism seen as reversible reddish-brown to blue color changes. The decreased donor-acceptor distance in (BPA4)4[Fe(CN)6] enhanced charge-transfer interaction allowing charge separation via one-electron transfer, as evidenced by in-situ ESR and FTIR spectroscopies. The reversibility of hydrochromic behavior was demonstrated by in-situ HT-XRPD, hot-stage microscopic and in situ diffuse-reflectance spectroscopic analyses. The insight into electronic structural features was obtained with density functional theory calculations, employed to elucidate electronic structure for both compounds. The electrical properties of the phases during dehydration process were investigated by temperature-dependent impedance spectroscopy.